Evaluation of YouTube videos addressing thoracoscopic sympathectomy using the LAP-VEGaS guidelines - Adorisio, Ottavio; Davoli, Enrico; De Peppo, Francesco (Frontiers in Surgery, 2023)
Introduction The study aims to evaluate the quality of videos addressing thoracoscopic sympathectomy on YouTube® using the LAParoscopic surgery Video Educational GuidelineS (LAP-VEGaS) criteria. Methods YouTube was searched using the following keyword: “thoracoscopic sympathectomy” on August 22, 2021. The first 50 videos were analyzed and classified for baseline characteristics and conformity to the LAP-VEGaS checklist. Results Duration ranged from 19 seconds to 22 minutes. The mean number of likes was 14.8 (range 0-80). The mean number of dislikes was 2.5 (range 0-14). The mean number of comments was 8.5 (range 0-67). Nineteen videos did not meet our criteria and were excluded. Regarding the remaining 31 videos, none contained all 16 points of the LAP-VEGaS essential checklist (mean 5.4 points, range 2–14 points), with almost all neglecting preoperative information and outcomes. The mean percentage of conformity was 37% (range 12%–93%). The most viewed videos were not associated with higher conformity to LAP-VEGaS criteria showing only 4/16 points (25%). Conclusions The quality of videos addressing TS on YouTube®, based on the LAP-VEGaS checklist may be considered not acceptable. Experienced surgeons and surgeons in trainees should be aware of this when using it as a learning resource in their clinical practice.